2017
DOI: 10.17243/mavk.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

Agrártájhoz kötődő madárfajok („farmland birds”) állományának változása, helyzete Európában

Abstract: The present review aimed to summarize the available evidence on farmland bird populations and their changes over the past decades in Europe. Firstly, a short historical background of the European agricultural intensity is presented. Secondly, the European Farmland Bird Index, published papers and grey literatures were searched and studied to show the recent population trends and population sizes of farmland bird species (37 species selected for monitoring by the EU and more specifically focusing on 10 bird spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Numerous detailed studies in recent decades have reported on declining farmland songbird populations, including Tucker and Heath (1994), Siriwardena et al (1998), Pitkänen & Tiainen (2001), Gregory et al (2004), Newton (2004b), Wretenberg et al (2006), Reif et al (2008) and Báldi and Batáry (2011). Agricultural intensification is the main reason behind the large-scale decrease (Verhulst et al 2004, Németh 2017. Such intensification comprises large homogeneous fields, increased isolation of habitat patches due to the conversion of previously unused land to production, lack of bushes on field edges, the application of a large number of pesticides, chemicals and fertilisers, heavy mechanisation or overgrazing (Hallmann et al 2014, Traba & Morales 2019, Valavanidis 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous detailed studies in recent decades have reported on declining farmland songbird populations, including Tucker and Heath (1994), Siriwardena et al (1998), Pitkänen & Tiainen (2001), Gregory et al (2004), Newton (2004b), Wretenberg et al (2006), Reif et al (2008) and Báldi and Batáry (2011). Agricultural intensification is the main reason behind the large-scale decrease (Verhulst et al 2004, Németh 2017. Such intensification comprises large homogeneous fields, increased isolation of habitat patches due to the conversion of previously unused land to production, lack of bushes on field edges, the application of a large number of pesticides, chemicals and fertilisers, heavy mechanisation or overgrazing (Hallmann et al 2014, Traba & Morales 2019, Valavanidis 2021.…”
Section: Discussionmentioning
confidence: 99%